Parallelization of the N-queens problem : Load unbalance analysis. - De Giusti, Laura Cristina (2003)
The paper presents an analysis of three parallelization structures of the N-queens problem, taking into account N processors. The focus has been set on investigating the adaptation of the architecture structure to the proposed algorithm type, so as to study the load unbalance in each case, for which two different metrics have been established. The experimental results and the efficient implementation of the algorithms are discussed together with the related current research lines.